Extraction of tobacco extract from discarded tobacco leaves for cigarette yarns dyeing and neophytadiene separation - Wang, Long; Chen, Weihua; Wan, Yuqi; He, Aimin; Liu, Jiayin; Hu, Xuemin (Frontiers in Chemistry, 2025)
A continuous process integrating extracting valuable compounds from waste tobacco leaves for cigarette yarns dyeing and neophytadiene separation was developed, enabling sequential production of tobacco crude extract, colored yarns, tobacco-derived absolute, and neophytadiene. Systematic comparison of residues from four regions revealed that Lanxiong-derived biomass demonstrated the highest extract yield (25%), providing optimal raw material for scaled neophytadiene production. GC-MS and NMR analyses confirmed >98% purity and structural integrity of purified neophytadiene. When the crude extract was applied directly to cotton yarns dyeing, the dyed yarn with 1.5 wt% tobacco crude extract solution from Zunyi achieved a K/S value of 2.013 and exhibited a yellow-brown hue shift that met visual identification requirements for cigarette yarns. The dyed yarns retained over 90% tensile strength of untreated controls, while elongation and unevenness indices showed no statistically significant alterations. This integrated approach establishes a green and sustainable technological route for valorizing tobacco waste within circular economy frameworks.